Mechanical characterisation of hydrogen-induced quasi-cleavage in a metastable austenitic steel using micro-tensile testing. (1st March 2016) - Mine, Yoji; Koga, Kaoru; Kraft, Oliver; Takashima, Kazuki
Abstract: Micro-tensile tests were performed using single- and twinned bi-crystals with and without hydrogen pre-charging in a metastable austenitic steel to elucidate the occurrence of hydrogen-induced quasi-cleavage. The hydrogen-charged specimens exhibited in the stress–strain behaviour a stress decrease in the plateau region after yielding. In this stage, a lamellar microstructure of martensite was formed within the parent austenite. Fracture occurred as quasi-cleavage along the habit planes of the martensite lamellae. A mechanism is proposed where the excess hydrogen generated by the martensitic transformation of hydrogen-containing austenite concentrates into the retained austenite between the martensite laths, promoting the localised deformation to fracture. Graphical abstract: